ECONOMIC TYPOLOGY APPROACH TO CALCULATE UNEMPLOYMENT INDEX AND REGIONAL POVERTY RATE (STUDY IN TAPAL KUDA AREA OF EAST JAVA) - Setyo Wahyu Sulistyono (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2018)
The aims of this study is determining the level of unemployment index then linking the calculation of the unemployment and poverty index through mapping the economic typology, so in the end determining the form of government intervention on the solution of rigidity in the labor market and its relation to poverty in the residency area. The location of research is the area of East Java that called